Quantum chemical characterization and In Silico evaluation of Allicin and Trigonelline as EED inhibitors: A DFT, molecular docking, and ADMET study - Budha, Bishal; Khanal, Madan; Acharya, Arjun (BIBECHANA, 2026)
Aberrant regulation of Polycomb Repressive Complex 2 (PRC2), a key epigenetic modulator, is strongly linked to oncogenesis, making it a therapeutic target for epigenetic interventions. Among inhibition strategies, selectively interfering with Embryonic Ectoderm Development (EED), a core PRC2 subunit, has shown greater specificity and efficacy than direct EZH2 inhibition. In this context, two phytochemicals, Allicin and Trigonelline, previously reported for anticancer activities, were investigated for potential interaction with EED. Density Functional Theory (DFT)-based quantum chemical analyses, including HOMO-LUMO energy levels, energy gaps, and global reactivity descriptors, were employed to assess chemical reactivity. Molecular electrostatic potential (MEP) surfaces and Mulliken charge distributions further elucidated electronic behavior and charge localization. Molecular docking simulations revealed that Allicin and Trigonelline bind effectively to EED, with binding affinities of –3.82 and –3.89 kcal/mol, respectively. Taken together, these findings highlight their potential as lead probes for PRC2-targeted therapy, supported by favorable ADMET profiles.